2018
DOI: 10.1007/s11249-018-1032-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Friction in Lubricant-Surface Systems for High-Performance Transmissions Under Mild Wear

Abstract: The lubricant-surface system is complex in nature and can significantly affect the frictional performance of high-performance transmission systems. The complexity stems from the coupled mechanical and chemical phenomena that occur at the interfacial tooth conjunctions. A combined analytical and precision experimental approach is presented to analyse the salient parameters of the lubricant-surface system. A multiscale procedure comprising topographical measurement, pin-on-disc tribometry, atomic force microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It has been shown that under severe conditions, where physically-adsorbed layers may be removed completely or partially during the sliding process, the results obtained from dry LFM for the pressure coefficient of boundary shear strength may be more deemed to be more appropriate [82]. However, the changes in the frictional behaviour in micro-scale can also be linked to the changes in the surface topography resulting from the removal of the surface-adsorbed layers.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that under severe conditions, where physically-adsorbed layers may be removed completely or partially during the sliding process, the results obtained from dry LFM for the pressure coefficient of boundary shear strength may be more deemed to be more appropriate [82]. However, the changes in the frictional behaviour in micro-scale can also be linked to the changes in the surface topography resulting from the removal of the surface-adsorbed layers.…”
Section: Resultsmentioning
confidence: 99%
“…A precision in-house manufactured uni-directional pin-on-disc tribometer ( Figure 1) replicates some aspects of high performance transmission gear meshing contacts through representative contact conditions [29]. The applied normal load on the disc sample through the pin is generated by a dual cantilever loading mechanism, resulting in a circular point contact.…”
Section: Tribometrymentioning
confidence: 99%
“…A Ktype thermocouple feedback loop is used to maintain/regulate the surface temperature of the samples. A syringe driver supplies a fixed rate of lubricant feed onto the sample surface with the height of the inlet meniscus controlled by a roller wiper system [29]. Therefore, repeatable conditions are assured for all the reported experiments.…”
Section: Tribometrymentioning
confidence: 99%
See 2 more Smart Citations